Zootechnical performance of Girolando cattle at Kpinnou Breeding Farm, South-West of Benin Republic - Alassane, Yacoubou; Ahounou, Serge Gbênagnon; Toleba, Soumanou Seibou; Adjakpa, Achille Amour; Dotche, Ignace Ogoudanan; Houaga, Isidore; Moula, Nassim; Antoine-Moussiaux, Nicolas; Hornick, Jean-Luc; Youssao, Abdou Karim Issaka (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The aim of the study was to assess the weight and reproductive performances of Girolando cattle at Kpinnou Breeding Farm (KBF) in the south western of Benin Republic. Materials and methods: The weight performance and body measurements were taken on a total of 150 Girolando cattle. The study of the reproductive traits was based on the recorded demographic indicators between 2012-2013 of 67 cows. Results: From calving to the age of 3 months, the monthly average weight of calves did not vary with the season of calving (P>0.05). Between the 4th and 9th month, the weight varied with the birth seasons and the sex of the calf. Beyond 9th month, the calf’s average weight was the same regardless the calving season. At the age of 24 months, the highest weight (393.33 kg) was obtained during the long rainy season. The highest average weight was 398.22 Kg for males against 364.25 Kg for females at 24 months. The fertility rates ranged from 91.18% to 100% and the fecundity rate ranged from 85.29% to 103% during the study period. The apparent fertility rate was 91.18%. As for the calving and abortion rates, they were 93.55% and 6.45%, respectively. The mortality rate before weaning was 6.90% while the weaning viability was 93.10%. Calving occurred from January to June and from August to December. Conclusion: In overall, the Girolando performances are satisfactory and show a good adaptation at KBF. http://doi.org/10.5455/javar.2018.e255